Global mass fixer algorithms for conservative tracer transport in the ECMWF model - M. Diamantakis; J. Flemming (Geoscientific Model Development, 2014)
Various mass fixer algorithms (MFAs) have been implemented in the Integrated Forecasting System (IFS) of the European Centre for Medium-Range Weather Forecasts (ECMWF) to ensure mass conservation of atmospheric tracers within the semi-Lagrangian (SL) advection scheme. Emphasis has been placed in implementing schemes that despite being primarily global in nature adjust the solution mostly in regions where the advected field has large gradients and therefore interpolation (transport) error is assumed larger. The MFAs have been tested in weather forecast, idealised and atmospheric dispersion cases. Applying these fixers to specific humidity and cloud fields did not change the accuracy of 10-day forecasts. In other words, global mass tracer conservation is achieved without deteriorating the solution accuracy. However, for longer forecast timescales or for forecasts in which correlated species are transported, experiments suggest that MFAs may improve IFS forecasts.